Y-TZP surface behavior under two different milling systems and three different accelerated aging protocols - Dal Piva, Amanda M. [UNESP]; Tribst, Joao Paulo [UNESP]; Gondim, Laisa D.; Ribeiro, Isabella L.; Campos, Fernanda; Arata, Anelyse; Souza, Rodrigo O. (Edizioni Minerva Medica, 2018)
BACKGROUND: To evaluate the influence of aging and milling system on zirconia surface roughness (SR) and phase transformation. METHODS: Eighty crowns were divided in two groups according to yttria-stabilized tetragonal zirconia polycrystalline (Y-TZP) ceramic milling system (CAD-Neodent or MAD-Zirkonzahn). The crowns were submitted to different aging protocols (N.=10): 1) no aging; 2) autoclaving; 3) pH cycling; or 4) thermocycling. Next, the samples were submitted to an optical profilometry analysis to determine differences in the S R (um). A n X-ray diffraction analysis (XRD) was performed to quantify the percentage of monoclinic phase transformation. SR data was analyzed by two-way A NOVA (a=0.5%). RESULTS: Aging protocol (P=0.42) and milling system (P=0.08) had no influence on the SR. However, the number of monoclinic phases was influenced by the autoclaving and pH cycling. CONCLUSIONS: The surface roughness of zirconia-based crowns was not influenced by low temperature degradation or milling system. Regarding the phase transformation, autoclaving and pH-cycling aging presented a monoclinic phase increase when compared to the control group and thermocycled groups.
Keywords: Dental materials; Prosthodontics; Surface properties; Yttria-stabilized tetragonal zirconia